PERANCANGAN DAN PEMBUATAN SERTA PENGUJIAN (KELAYAKAN) KEBERFUNGSIAN ALAT MENGUKUR SUHU FLUIDA PADA PRAKTIKUM SUHU DAN KALOR - Herlina lanto; Marianus; Jeane Cornelda Rende (Charm Sains: Jurnal Pendidikan Fisika, 2021)
This research was motivated by the lack of availability of tools and practical guides for measuring fluid temperature, which made it impossible to conduct practical activities. The aim of this research is to develop a tool for measuring liquid temperature that is suitable for practical activities in the UNIMA physics laboratory. This research is a research development (research and development) that consists stages, namely preliminary studies, literature research, design of internship tools, production of internship tools, validation of experts/ experts, revision 1 (improvement 1), functionality test, validation of experts/ emperts, revision 2 (improvement 2) and reporting. The data was collected through experiment and expertvalidation. The test results of the practical tool for measuring the temperature of this liquid show the highest percentage of errors at 2,3%, while the validation by materials experts and media experts for tools and practical guides for measuring the liquid temperature is in the range of 90-100%. Based on the results of the study, it can be concluded that a tool and practical guide for measuring fluid temperature with valid or proper qualifications has been created.